The Management of Intergroup Conflicts in Selected Universities in Southwestern Nigeria - Osezua, Ehiyamen Mediayanose (2015)
This study examined intergroup conflicts in selected universities in Southwestern Nigeria and identified their causes. This was with a view to examine its effects on the universities and proffering appropriate management strategies in resolving them.